Quantitative analysis of the mechanical environment in the embryonic heart with respect to its relationship in cardiac development - Bulk, Alexander T., author; Dasi, Lakshmi Prasad, advisor; Garrity, Deborah, advisor; Popat, Ketul, committee member; Orton, Christopher, committee member (Colorado State University. Libraries, 2015)
In order to understand the causes of congenital heart defects, which afflict at least 4 infants per 1,000 live births, research has implemented the use of animal models to study embryonic heart development. Zebrafish (Danio rerio) have become one of the more prominent of these animal models due to the fact that their heart morphology at the earliest stages of development is remarkably similar to humans, and because embryos lack pigmentation, rendering them transparent. This transparency allows for high-speed images of blood flow to be acquired in the developing heart so that the mechanotransductive relationship between the intracardiac flow environment and myocardial progenitor cell differentiation can be understood. One particular aspect of the flow environment, a cyclic retrograde flow at the junction of the forming atrium and ventricle, has been shown to be necessary for valve formation, though the mechanisms causing it to occur had previously been unknown. By comparing the results of two-dimensional spatiotemporal analysis applied to embryos both with normal retrograde flow and inhibited retrograde flow, this study shows that a particular range of pressures associated with the pumping mechanics of the heart as well as resistance due to systolic contractile closure must exist in order to maintain adequate retrograde flow to induce valve formation. The use of two-dimensional spatiotemporal analysis was sufficient to acquire these results, however when applied to analysis of other aspects of the intracardiac flow environment, this computational method is subject to critical limitations. Therefore, this study includes the development of methodology to integrate the results of spatiotemporal analysis on multiple focal planes bisecting the heart into a more accurate, three-dimensional result. The results of this study not only increase our understanding of the mechanics behind an important factor in embryonic development, but also enable future experiments pertaining to the measurement of embryonic intracardiac blood flow to be performed with increased certainty.
Keywords: embryonic; focal plane; heart development; mechanotransduction; transcription; zebrafish